Predicting survival in chronic lymphocytic leukemia. Issue 3 (March 2012) - Bazargan, Ali; Tam, Constantine S; Keating, Michael J
There is increasing interest in the use of prognostic markers that may predict survival and guide management in patients diagnosed with the early stages of chronic lymphocytic leukemia (CLL). Currently, the most important traditional prognostic factors include clinical staging, lymphocyte doubling time and ββ2-microglobulin/thymidine kinase; and the most important novel markers include karyotypic aberrations (typically assessed by FISH probes or CpG oligonucleotide karyotyping) and IgVH mutation status. Although each of these factors have individually shown significant correlations with survival, there is increasing appreciation that the most complete information may be obtained by using a combination of several factors in prognostic normograms or models. In this article, we review the current state-of-the-art with regards to CLL prognostic factors and discuss how they can be applied in the clinic.